Correction: Modelling vaccination strategies against Rift Valley fever in livestock in Kenya - Gachohi, John M.; Njenga, M.K.; Kitala, P.; Bett, Bernard K. (Public Library of Science, 2017)
This corrects the article DOI: 10.1371/journal.pntd.0005049